Development and evaluation of a droplet digital PCR assay for the diagnosis of paucibacillary leprosy in skin biopsy specimens. - Xiujun Cheng; Lele Sun; Qing Zhao; Zihao Mi; Gongqi Yu; Zhenzhen Wang; Yonghu Sun; Chuan Wang; Chunhua Man; Fanghui Fu; Hong Liu; Furen Zhang (Public Library of Science (PLoS), 2019)
BACKGROUND:The reduced amounts of Mycobacterium leprae (M. leprae) among paucibacillary (PB) patients reflect the need to further optimize methods for leprosy diagnosis. An increasing number of reports have shown that droplet digital polymerase chain reaction (ddPCR) is a promising tool for diagnosis of infectious disease among samples with low copy number. To date, no publications have investigated the utility of ddPCR in the detection of M. leprae. The aim of this study was to develop and evaluate a ddPCR assay for the diagnosis of PB leprosy. METHODOLOGY:The two most sensitive DNA targets for detection of M. leprae were selected from electronic databases for assessment of sensitivity and specificity by quantitative polymerase chain reaction (qPCR) and ddPCR. Control patients (n = 59) suffering from other dermatological diseases were used to define the cut-off of the duplex ddPCR assay. For comparative evaluation, qPCR and ddPCR assays were performed in 44 PB patients and 68 multibacillary (MB) patients. PRINCIPAL FINDINGS:M. leprae-specific repetitive element (RLEP) and groEL (encoding the 65 kDa molecular chaperone GroEL) were used to develop the ddPCR assay by systematically analyzing specificity and sensitivity. Based on the defined cut-off value, the ddPCR assay showed greater sensitivity in detecting M. leprae DNA in PB patients compared with qPCR (79.5% vs 36.4%), while both assays have a 100% sensitivity in MB patients. CONCLUSIONS/SIGNIFICANCE:We developed and evaluated a duplex ddPCR assay for leprosy diagnosis in skin biopsy samples from leprosy patients. While still costly, ddPCR might be a promising diagnostic tool for detection of PB leprosy.